WORKSHOP PENANGANAN OLI BEKAS DI BENGKEL HARLEY DAVIDSON KABUPATEN SEMARANG - Sofia Nabila; Fathoni Firmansyah; Anggreini Beta Citra Dewi; Taufan Arif Zulkarnain (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2023)
Harley Davidson reparation produces large amounts of waste oil every day around 3 liters per motorcycle. Waste oil decreases a change in composition or chemical composition after being used for a long time. This is because there is a mixture of dirt, gasoline, and also influenced by pressure and temperature when used. The purpose of this activity is to obtain waste oil storage conditions and can be used as a reference that can support solving problems related to waste oil storage. The method of this program is to provide counseling on how to accommodate the oil that comes out of the motor up to the storage stage by Government Regulation No. 22 of 2021. The expected result is that the management of hazardous and toxic material waste in workshops can be carried out properly and the creation of a workshop environment that is safe, comfortable, and free from environmental pollution.